IMPACT OF EXPERIMENTAL TEACHING METHOD “LANGUAGE THROUGH SPORT” ON MOTIVATIONAL STRATEGIES OF WEIGHTLIFTING SPECIALISTS - Е. Mileva; V. Slavova; N. Yankova; V. Panayotov (Trakia Journal of Sciences)
Recently, there have been outlined some problems in the motivated participation of students in the educational process. These ones presuppose the optimization of traditional teaching methods and the application of new methods, techniques and approaches in the learning process. The necessity of introducing a new-invented educational model for students’ training at NSA "Vasil Levski", combining the foreign language teaching and their sports training is imposed by the need to improve the existing educational practice both in sport practice and in foreign language learning. The new-invented teaching method "Language through sport" for weightlifting and power lifting specialists has not been developed so far in this specific educational context. The experimental teaching method has been elaborated and applied by simultaneous implementation of foreign language learning of standardized international terms in the field of weightlifting and power lifting in students’ training sessions. The study of the impact of new-invented method "Language through Sport" on students’ motivation is a reliable indicator of the efficacy of this training and teaching method in sports pedagogical practice, not only in weightlifting and power lifting but also in other sports disciplines.